2010
DOI: 10.2106/jbjs.i.01518
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Tranexamic Acid Reduces Postoperative Blood Loss in Total Knee Arthroplasty

Abstract: At the conclusion of a total knee arthroplasty with cement, topical application of tranexamic acid directly into the surgical wound reduced postoperative bleeding by 20% to 25%, or 300 to 400 mL, resulting in 16% to 17% higher postoperative hemoglobin levels compared with placebo, with no clinically important increase in complications being identified in the treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
434
3
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(483 citation statements)
references
References 42 publications
18
434
3
28
Order By: Relevance
“…A single intraoperative local application decreased the total blood loss, which was significant, but not the drain loss. Wong et al [31] reported the same findings. Therefore, a singledose regimen, which is widely used, is not the most effective regimen.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…A single intraoperative local application decreased the total blood loss, which was significant, but not the drain loss. Wong et al [31] reported the same findings. Therefore, a singledose regimen, which is widely used, is not the most effective regimen.…”
Section: Discussionsupporting
confidence: 56%
“…If however one elects to use just a single dose, then local application is recommended rather than an intravenous dose. Local tranexamic acid application would avoid problems associated with systemic absorption [31] and it would take care of the reported fibrinolysis that predominantly is activated locally in the surgically treated tissue [26]. Our study also showed the total blood loss was reduced with local application.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Systemic tranexamic acid may be a more effective approach [7] but may also be associated with some risks, although recent systematic reviews have failed to demonstrate any difference in adverse events associated with the use of tranexemic acid [1,19]. Topical application of tranexamic acid has been shown to reduce postoperative blood loss [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons évalué si la mise en oeuvre d'un protocole qui faciliterait l'administration universelle de TXA chez les patients subissant une arthroplastie totale du genou ou de la hanche réduirait l'incidence de transfusion d'érythrocytes sans augmenter les complications cliniques. Méthode Nous avons mis en oeuvre une politique de qualité des soins afin de procéder à l'administration universelle de TXA par voie intraveineuse à une dose de 20 mgÁkg -1 à tous les patients admissibles subissant une arthroplastie totale de la hanche ou du genou entre le 21 Administration of tranexamic acid (TXA) has been shown to reduce blood loss and allogeneic red blood cell (RBC) transfusion in cardiac and various noncardiac surgical procedures. 1 Many randomized controlled trials, [2][3][4][5][6] systematic reviews, and meta-analyses [7][8][9][10][11] have shown that systemic and topically administered TXA reduces allogeneic RBC transfusion in hip or knee arthroplasty surgery.…”
Section: Résuméunclassified